2011
DOI: 10.1111/j.1752-0606.2009.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration: Family and therapist perspectives of helpful therapy

Abstract: This qualitative study examined how a group of families and their therapists described helpful therapy. The qualitative analysis generated family and therapist perspectives. As a double description, the therapist and family perspectives highlighted conversation, participation, and relationship as three core areas of helpful therapy. These are specified by categories and subcategories that center upon activities of sharing experiences, contributing own knowledge and personal involvement, posing questions, refor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 24 publications
(34 reference statements)
4
53
0
6
Order By: Relevance
“…Feedback from service users is necessary in order to conclude that collaboration is taking place. This relationship between collaboration and feedback was confirmed by Sundet (2011). In the study reported here, this was explicated through a set of conversational types: conversations targeting information from the client that can be fed back to the therapist, and the surplus conversations to which these tools give rise.…”
Section: Collaborationmentioning
confidence: 56%
See 1 more Smart Citation
“…Feedback from service users is necessary in order to conclude that collaboration is taking place. This relationship between collaboration and feedback was confirmed by Sundet (2011). In the study reported here, this was explicated through a set of conversational types: conversations targeting information from the client that can be fed back to the therapist, and the surplus conversations to which these tools give rise.…”
Section: Collaborationmentioning
confidence: 56%
“…Sundet (2011) connects this venture to the language oriented therapies and suggests how these manners of working are expanded through a family perspective.…”
Section: Collaborationmentioning
confidence: 96%
“…There are currently efforts underway to determine how best to integrate feedback to guide psychotherapist practice (e.g., Lambert et al, 2001, 2002, Sundet, 2011; see Sundet, 2012 for a review) and to implement what is often referred to as “measurement-based care” in large community mental health centers (Lewis et al, 2015). For instance, humanistic psychotherapy research focused on the role of different types of session outcomes, such as a session’s helpfulness, depth and smoothness, as immediate feedback for therapists.…”
Section: Cognitive Processes Underlying Clinical Judgments (Box 3)mentioning
confidence: 99%
“…However, there remains a lack of research exploring client experiences of SDM in psychotherapy. Findings from one study are available from a grounded theory analysis of family psychotherapy in a Norwegian outpatient setting . Families reported that one helpful aspect of their treatment was having choice around the organization of the therapeutic work.…”
Section: Introductionmentioning
confidence: 99%